RESPON MASYARAKAT TERHADAP MANTAN NARAPIDANA PENYALAHGUNAAN NARKOBA DI DESA MELAYU BESAR KECAMATAN TANAH PUTIH TANJUNG MELAWAN KABUPATEN ROKAN HILIR - Trisna Safitri; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study was held at Big Malay village in Tanah Putih Tanjung District against Rokan Hilir Regency. The purpose of this research is to know the driving factor of drug abuse behaviour in the big Malay village of Tanjung Putih subdistrict against Rokan Hilir Regency. The topic of focus of this research is the public response to former convicts in the Big Malay Village, Tanah Putih Tanjung fight. The authors use quantitative methods and use accidental sampling techniques. Data instruments are observations, interviews, polls and documentation. Studies have found that there are several driving factors for drug abuse in the large Malay village, as follows: internal factors, internal factors that encourage drug abuse are education and invidu. Studies have found that there are several driving factors for drug abuse in the large Malay village: the internal factors that encourage drug abuse are education and invidu. Research conducted found that 43.1% of respondents did not end SD, and 56.9% of respondents did not end junior high school. It can be concluded that the respondent also did not graduate. Research finds that all respondents experience dropouts. The reason that causes the end to use drugs is because the respondent felt depressed by the surrounding environment (49.0%). External fakors that encourage drug abuse are a state of economy and social environment. 49% of respondents had the money to buy such drugs from their parents. Studies have also found that 88.2% of respondents associate with their colleagues who also use drugs. Keywords: Deviant Behaviour, Response, Drugs